Personal responsibility within health policy: unethical and ineffective - Friesen, Phoebe (Journal of medical ethics, 2018)
This paper argues against incorporating assessments of individual responsibility into healthcare policies by expanding an existing argument and offering a rebuttal to an argument in favour of such policies. First, it is argued that what primarily underlies discussions surrounding personal responsibility and healthcare is not causal responsibility, moral responsibility or culpability, as one might expect, but biases towards particular highly stigmatised behaviours. A challenge is posed for proponents of taking personal responsibility into account within health policy to either expand the debate to also include socially accepted behaviours or to provide an alternative explanation of the narrowly focused discussion. Second, a critical response is offered to arguments that claim that policies based on personal responsibility would lead to several positive outcomes including healthy behaviour change, better health outcomes and decreases in healthcare spending. It is argued that using individual responsibility as a basis for resource allocation in healthcare is unlikely to motivate positive behaviour changes, and is likely to increase inequality which may lead to worse health outcomes overall. Finally, the case of West Virginia's Medicaid reform is examined, which raises a worry that policies focused on personal responsibility have the potential to lead to increases in medical spending overall.